Ethics of Migration Research Methodology : Dealing with Vulnerable Immigrants. - van Liempt, Ilse (Liverpool University Press, 2009)
Intends to present the difficulties that researchers working with migrants in precarious situations have to contend with, and to contribute to the development of methodological and ethical discussions relevant to the topic of migration as an interdisciplinary field of research. This book is suitable for those dealing with vulnerable migrants.